Impact of Rice Price Fluctuations on the Welfare of Paddy Farmers - Rizka Putri Fadilah; Sri Widayanti; Hamidah Hendrarini (The University of Lampung, 2025)
Rice is a staple food for Indonesia and should be available at an affordable price. This study aims to analyze the factors causing fluctuations in rice prices, and analyze the effect of changing prices on the livelihoods of rice farmers. The farmers’ welfare was calculated using Farmer Exchange Rate (FER). The analysis was conducted using a simultaneous equation model, utilizing time series data from 2009 to 2023. This study employed Two-Stage Least Squares (2SLS) and Multiple Linear Regression techniques. The findings reveal that rice production is significantly influenced by the previous year’s rice prices and the size of the harvested area. Meanwhile, the factors affecting consumption are the rice price variable and income levels, as well as the factors influencing rice prices, which include the price of unmilled dry grain, rice production, and the highest retail price. Meanwhile, regarding the welfare of rice farmers measured by the FER, it is known that the FER in East Java has fluctuated from 2009 to 2023. The highest contributor to the rice FER occurred in 2023, reaching 115.64%, with an average FER for East Java from 2009 to 2023 of 102.86%. This indicates that the Rice FER is in a surplus state, suggesting that rice farmers are prosperous.